Whole-Body Vibration Exposure vis-à-vis Musculoskeletal Health Risk of Dumper Operators Compared to a Control Group in Coal Mines - Kumar V.; Palei S.K.; Karmakar N.C.; Chaudhary D.K. (My University, 2025)
Background: Whole-body vibration (WBV) exposure of coal mine dumper operators poses numerous health hazards. The case-control study was aimed at assessing the relative musculoskeletal health risk of dumper operators' exposure to WBV with reference to the nonexposed group. Methods: Measurements of WBV exposure were taken at the operator–seat interface using a human vibration analyzer for 110 dumper operators in three coal mines. This vibration measurement was supplemented by a questionnaire survey of 110 dumper operators exposed to WBV and an equal number of workers not exposed to WBV. The relative risk of musculoskeletal disorders (MSDs) has been assessed through the case-control study design. Results: ISO guidelines were used to compare the health risk. It was observed that the prevalence of pain in the lower back was 2.52 times more in the case group compared to the control group. The case group of Mine-2 was 2.0 times more prone to vibration hazards as compared to Mine-3. Conclusion: The case group is more vulnerable to MSDs than the control group. The on-site measurement as well as the response of the dumper operators during the questionnaire survey corroborates this finding. © 2021 The Authors